Esophageal Neuroendocrine Carcinoma With Focal Squamous Cell Carcinoma Component - Min Kyun Kang; Do Kyun Kang (SAGE Publishing, 2020)
This study was about a 70-year-old man with progressive dysphagia. Esophagogastroduodenoscopy showed a 1.2-cm circumferential ulcerative mass at the level of 23 cm from the upper incisors in the upper esophagus. The mass was first diagnosed as a poorly differentiated squamous cell carcinoma. McKeown esophagogastrectomy was performed with intention to treat the lesion. The pathological examination showed an esophageal neuroendocrine carcinoma that was mixed with squamous cell carcinoma component. In this report, we present a unique case of the extremely rare esophageal neoplasm, an esophageal neuroendocrine carcinoma with squamous cell carcinoma component.